The Significance of Interslavonic Language Contacts in the Formation of a New Type of Literary Russian - Garbul, Liudmila (Respectus Philologicus, 2013)
This article presents facts verifying the presence of nearly 1,000 lexical and over 300 semantic Polonisms found in the Russian chancery language (diplomatic correspondence) of the Muscovite state of the end of 16th and the first half of the 17th centuries, and draws conclusions about the role of the Polish influence on the Russian written language at that time and thereafter. According to our data, the Polish influence on the Russian written language in the first half of the 17th century extended both in terms of quantity and quality as well, which led to the close interaction of the lexical and semantic systems of the contiguous languages on a deeper level. This, in our opinion, allows us to discuss the fact that the production of the Posolsky Prikaz (ambassadorial office) in the second half of the 16th–17th centuries acted not only as one of the main channels of the Polonisation of Russian lexis, but—due to the rather large amount of semantic borrowings, as well as the increasing number of intraslavonic derivates among lexical borrowings in the 17th century— encouraged the extension of the influence of Polish culture in a broader aspect as well. This was reflected in the strategy of the formation of Muscovite Russian language policy, when the southwestern Russian language, which in its turn represented the borrowing of the Polish language situation, was being transformed onto the Great Russian soil. It should be pointed out that the prostaja mova, which—due to the absence of its equivalent in Great Russian conditions—played a great role and acted as an active mediator in Polish–Russian language contacts, influenced the chancery language of the Muscovite state, especially diplomatic correspondence.
Keywords: Chancery Language; Polish–Russian Language Contacts; Lexical Polonisms; Semantic Polonisms; Prostaja mova